Polpa de cajá em pó obtida pelo processo de secagem em leito de jorro: caracterização física, fisico-quimica e estudo da estabilidade. - Ferreira, Ana Paula Rodrigues (2017)
Among the fruits produced in Brazil, caja is economically relevant due to its sensorial characteristics (differentiated flavor and aroma) and nutritional quality (rich in antioxidant compounds). However, due to its perishbility, it is necessary to apply a technological process to maintain post-harvest quality of this fruit. The drying process in the stream bed is a good alternative to obtain pulp in the form of powder, using temperatures below 100ºC, which avoids high losses of thermo sensitive compounds present in the food, contributing to improve the using of the fruit, with added value of the raw material and product availability throughout the year. This research aims the production of powdered cashew pulp by drying in a jet bed and also physical, chemical-chemical and morphological characterization of the product obtained, including a study on the stability of the pulp in two types of packing (polyethylene and aluminum). The pulp of caja was used as raw material and as adjuvant of drying to maltodextrin (DE ≤20) in dryer bed of jet. The drying condition (temperature of 87 ° C, maltodextrin concentration of 12% and drying air flow of 1.6 m3/min) was determined by experimental design (central rotational composite 23) for stability study counting on lower moisture content. The morphologic study showed that the particles of the powder obtained present certain heterogeneity in the size and predominance of the spherical size and a smooth surface, being these characteristics important for the stability of the powder. The density presented an increase according to the level of consolidation applied and the powder presented cohesive behavior. The GAB model was the one that fits the best to the adsorption isotherms of the pulp powder. The stability during 90 days of the powder allows to identify the polyethylene packing did not avoid the water absorption, promoting a greater increase in the moisture content and the water activity. The use of the vacuum aluminum packing proved effective as a barrier against moisture absorption, favored a higher final concentration in the ascorbic acid content and a better percentage of solubility of the powders during storage. In this way, it can be noticed the drying of cashew pulp in the jet bed results in obtaining a powder with satisfactory physical and chemical-physical characteristics and that the use of the aluminum packing is more efficient in maintaining the quality of the product in powder.